Aspek Sosial Dan Lingkungan Pada Kejadian Luar Biasa (KLB) Chikungunya (Studi Kasus KLB Chikungunya di Kelurahan Bulusan Kecamatan Tembalang Kota Semarang) - Wuryanto, M.Arie (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2009)
Background: Chikungunya is a disease which has potentially outbreak in the community. Based on the community report since April 4th to May 16th, 2008, there were 53 cases of chikungunya occurred at Bulusan, sub-district of Tembalang. The aim of the study is to identify social and environment factor influence the occurrence of Chikungunya outbreak in the community.Method: It was a cross sectional study, employed qualitative and quantitative method which involved 53 cases and community members who lived in radius 100 meter from cases.Result:.This study found that there was an outbreak of chikungunya in Bulusan Village, Subdistrict of Tembalang, Semarang. Community members’ knowledge in preventing and controlling the disease were still lacking. Likewise, their practice in eliminating mosquito breeding place also showed a poor quality. Unsupported environment such as the existence of vegetations which cause humid temperature also influenced the occurrence of chikungunya outbreak in the community.Keyword : Chikungunya disease, social, environment, epidemiology.